Beneficios de la fisioterapia mediante la aplicación del movimiento y del masaje en pacientes del asilo de ancianos de la ciudad de Riobamba, periodo julio- diciembre 2011 - Colcha, Sonia (2013)
This research work with the theme: "Benefits of physiotherapy by applying motion and massage on patients at the nursing home in the city of Riobamba, period, July-December 2011", was conducted in the province of Chimborazo Riobamba canton, in the Nursing Home, the same that is designed to demonstrate the effectiveness of the movement and massage in geriatric patients that establishment. This center provides asylum to patients with various musculoskeletal pathologies especially, is a center where although no staff support physiotherapy, but that is not enough time to follow up and timely individualized for each patient. Thus was the need to provide immediate and adequate care to people in need, for which the data was collected from 50 patients the same as prior to the evaluation were diagnosed with various diseases, of which we chose the common as: osteoarthritis of the hip, knee osteoarthritis, rheumatoid arthritis and osteoporosis, which are mainly the result of biological and pathological processes either by age and also due to poor lifestyle as a sedentary lifestyle to which they are subjected.